2021
DOI: 10.33789/talentos.8.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Uso Del Caucho De Neumáticos Triturados Y Aplicados Al Concreto: Una Revisión Literaria

Abstract: Los avances en la tecnología del concreto conducen a la búsqueda de materiales alternativos que brinden mejoras en las propiedades del concreto y al mismo tiempo colaboren con reducir la contaminación del medio ambiente. En este artículo se revisará las investigaciones publicadas en revistas científicas indexadas en la base de datos Scopus y SciencieDirect, que tienen como objetivo estudiar el uso del caucho de neumáticos triturados para la producción de concretos en general. Se discutirá las metodologías y té… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Some researchers found that sound absorption and noise reduction coefficient increased with increased replacement levels of more than 20% crumb rubber [12] [13] and suggested that the higher sound absorption of rubber-concrete is due to the increase of air voids in the concrete. On the other hand, the inclusion of rubber in the concrete results in greater durability and elasticity, which gives rise to its use in important areas such as impact absorber in the construction of road elements and sound, in sonic barriers and also in buildings earthquake resistant, etc [13]. In the present study, rubber from waste tires was introduced as a substitute for sand in the concrete using different proportions.…”
Section: Introductionmentioning
confidence: 94%
“…Some researchers found that sound absorption and noise reduction coefficient increased with increased replacement levels of more than 20% crumb rubber [12] [13] and suggested that the higher sound absorption of rubber-concrete is due to the increase of air voids in the concrete. On the other hand, the inclusion of rubber in the concrete results in greater durability and elasticity, which gives rise to its use in important areas such as impact absorber in the construction of road elements and sound, in sonic barriers and also in buildings earthquake resistant, etc [13]. In the present study, rubber from waste tires was introduced as a substitute for sand in the concrete using different proportions.…”
Section: Introductionmentioning
confidence: 94%
“…En la actualidad, las tecnologías de producción del concreto han mostrado un nuevo nivel no con el objetivo de facilitar el proceso de elaboración, sino con el fin de aportar mejoras a las propiedades del concreto y reducir la contaminación ambiental, ya que los recursos utilizados para la mezcla suelen influir negativamente en el medioambiente (Muñoz et al, 2021). Uno de los objetivos de la mejora de la tecnología es alcanzar una mayor eficiencia energética y reducir el consumo de materiales no renovables, el agua y los minerales.…”
Section: Importancia De La Tecnología Del Concreto En La Vida úTil De...unclassified